Feasibility of performing the 3‐minute step test with remote supervision in children and adolescents with cystic fibrosis: A comparative study - Fernanda Maria Vendrusculo; Gisele Apolinário daCosta; Maria Amélia Bagatini; Brenda Maria Henrique Maia Lemes; Carolina Aguiar Faria; Larissa Carvalhaes deOliveira; Evanirso da Silva Aquino; Márcio Vinícius Fagundes Donadio (Wiley, 2024)
ABSTRACT Importance The 3‐min step test is a simple option to monitor submaximal exercise capacity, although its use via remote video monitoring has not been investigated in children with cystic fibrosis (CF). Objective This study aimed to assess the feasibility and reproducibility of performing the 3‐min step test with remote supervision. Methods A cross‐sectional study including CF patients (6-18 years) from two CF services were performed. Demographic, anthropometric, clinical, and lung function data were collected and two 3‐min step tests were performed: (i) in‐person supervision, and (ii) remotely supervised by video monitoring. Before and after the tests, heart rate (HR), oxygen saturation (SpO2), and the Borg score for dyspnea and lower limb fatigue were monitored. Results Twenty‐three patients (10.7 ± 3.7 years) with a mean FEV1 of 89.5% ± 23.2% were included. There were no significant differences between tests, with mean differences (95% confidence intervals) in final HR of -3.3 (-8.9, 2.4), change in HR of -1.9 (-6.1, 2.1), final SpO2 of 0.3 (-0.4, 1.0), and final dyspnea of 0.1 (-0.8, 0.9). The intraclass correlation coefficient was 0.852 (final HR), 0.762 (final SpO2), and 0.775 (final lower limb fatigue). Significant and moderate correlations were found between tests for final HR (r = 0.75), change in HR (r = 0.61), and final SpO2 (r = 0.61). The Bland-Altman analysis showed a mean difference in final SpO2 between tests of 0.3% (limit of agreement -3.0%, 3.5%). Interpretation Physiological responses between tests were similar, indicating it was feasible to perform the 3‐min step test with remote supervision in CF children.